Pengaruh Lingkungan Kerja, Kompensasi dan Kepuasan Kerja Terhadap Motivasi Kerja Karyawan Browny Persian Petshop-Yogyakarta (Coopetition : Jurnal Ilmiah Manajemen, 2024)
Human Resources (HR) is the planner, mobilizer, and controller of the entire company. Therefore, the management, empowerment and welfare of employees need to be considered. HR can work effectively and efficiently, one of the factors is the state of a conducive and adequate work environment. In addition, quality compensation plays an important role in employee motivation. The purpose of this study is to analyze the effect of Work Environment, Compensation and Job Satisfaction on Work Motivation. The population in this study was 30 employees of Browny Persian Petshop Yogyakarta who were also respondents as a whole. Quantitative data were obtained through the distribution of questionnaires, using the Likert scale method. Furthermore, the collected data is analyzed using the SPSS program. The results of this study prove that these three variables have no effect on the work motivation of Petshop Browny Persian employees. But simultaneously the Work Environment, Compensation and Job Satisfaction have a significant positive effect on work motivation. The results of this analysis have implications for Browny Persian Petshop's managerial, related to the need to take measurable actions to increase employee motivation through proper management of the Work Environment, Compensation and Job Satisfaction.